Simple Microfluidic Paper-Based Analytical Device (μ-PAD) Coupled with Smartphone for Mn(II) Detection Using Tannin as a Green Reagent - Fidelis Nitti; Wendelina Archangela Ati; Philiphi de Rozari; Pius Dore Ola; David Tambaru; Luther Kadang (Universitas Gadjah Mada, 2023)
The development of a simple yet greener microfluidic paper-based analytical device (μ-PAD) for on-site detection of Mn(II) in various types of waters using tannin as a natural reagent was described. The μ-PAD consists of twelve detection zones, created on a Whatman Number 1 filter paper by a simple drawing technique using an acrylic watercolor. The detection of Mn(II) was based on the color change on the reaction zone due to the reaction between Mn(II) and the pre-deposited tannin. The μ-PAD image was captured by a portable smartphone detector, and the blue intensity was digitized using a color picker application to generate the reflectance as the analytical response. The proposed method was characterized by a linear dynamic range of 0.05–0.25 mg L−1 with the limit of detection (LOD) for the determination of Mn(II) of 0.026 mg L−1. The other analytical merits of the proposed method, such as precision (RSD, 1.107%), accuracy (E, 6.697%), and recovery (104–112%), were all comparable to the existing spectrophotometric methods. The method’s successful application to natural water samples from manganese mining sites aligns with the reference spectrophotometric method, indicating its good selectivity and accuracy without significant influence of commonly associated interfering ions.